DESIGN AND OPTIMIZATION OF COLUMN STRUCTURE OF TREE SHAPED PARKING GARAGE - WANG Juan; LI FengJie; GAO XinLong; ZHANG LiYong; LI TongJie (Jixie qiangdu)
In this paper, the structure design and optimization of the column of the tree-shaped parking garage are carried out. The base dimensions are 2.4 m、0.7 m and 8.5 m respectively. The simplified model of column takes into account the axial stress caused by the total weight FN of each component and the bending stress caused by the suspended loading plate and the vehicle. The maximum stress is easy to occur at the root of the column. The calculated results are 63.06 MPa, less than allowable stress 117.5 MPa, maximum deflection 8.93 mm, much less than standard value 113.90 mm. In order to meet the requirements of strength and deflection displacement, the penalty function method is used to optimize the size of the main support of the column, and the optimized model is measured and compared with the software analysis. Under the same working condition, the stress change data at the root of the column are collected by the test instrument and compared with the software analysis. The stress at the same position is less than 10% of the deviation between the measured and the simulated analysis results. The design and analysis of column structure are carried out by combining finite element analysis with actual stress test, and the mixed penalty function method is used to optimize the column structure. The results show that the method is effective. It provides some means and reference for the analysis of this kind of project.